A CD8 T Cell/Indoleamine 2, 3‐Dioxygenase Axis Is Required for Mesenchymal Stem Cell Suppression of Human Systemic Lupus Erythematosus1. Issue 8 (August 2014) - Wang, Dandan; Feng, Xuebing; Lu, Lin; Konkel, Joanne E.; Zhang, Huayong; Chen, Zhiyong; Li, Xia; Gao, Xiang; Lu, Liwei; Shi, Songtao; Chen, Wanjun; Sun, Lingyun
<x xml:space="preserve">Abstract</x> Objective Allogeneic mesenchymal stem cells (MSCs) exhibit therapeutic effects in human autoimmune diseases such as systemic lupus erythematosus (SLE), but the underlying mechanisms remain largely unknown. The aim of this study was to investigate how allogeneic MSCs mediate immunosuppression in lupus patients. Methods The effects of allogeneic umbilical cord–derived MSCs (UC‐MSCs) on inhibition of T cell proliferation were determined. MSC functional molecules were stimulated with peripheral blood mononuclear cells from healthy controls and SLE patients and examined by real‐time polymerase chain reaction. CD4+ and CD8+ T cells were purified using microbeads to stimulate MSCs in order to determine cytokine expression by MSCs and to further determine which cell subset(s) or which molecule(s) is involved in inhibition of MSC–mediated T cell proliferation. The related signaling pathways were assessed. We determined levels of serum cytokines in lupus patients before and after UC‐MSC transplantation. Results Allogeneic UC‐MSCs suppressed T cell proliferation in lupus patients by secreting large amounts of indoleamine 2, 3‐dioxygenase (IDO). We further found that interferon‐γ (IFNγ), which is produced predominantly by lupus CD8+ T cells, is the key factor that enhances IDO activity in allogeneic MSCs and that it is associated with IFNGR1/JAK‐2/STAT signaling pathways. Intriguingly, bone marrow–derived MSCs from patients with active lupus demonstrated defective IDO production in response to IFNγ and allogeneic CD8+ T cell stimulation. After allogeneic UC‐MSC transplantation, serum IDO activity increased in lupus patients. Conclusion We found a previously unrecognized CD8+ T cell/IFNγ/IDO axis that mediates the therapeutic effects of allogeneic MSCs in lupus patients.